Production and characterization of iron-chromium-zinc pigment based ceramic stain colour of red-brown shade (Bangladesh Journal of Scientific and Industrial Research, 2013)
Considering the demand of ceramic stain colours in Bangladesh, an attempt has been taken to develop iron-chromium-zinc pigment based ceramic stain colour of red-brown shade which could be used as an import substitute material in the local ceramic industries. The desired shade of red-brown stain was synthesized from an equimolar mixture of pure chromium oxide (Cr2O3), iron oxide (Fe2O3) and zinc oxide (ZnO). The developed stain was characterized by X-ray diffraction (XRD) technique. The characteristic of the stain complied with the chemical durability. Moreover, chromium leaching was below the permissible exposure limit which makes it as a promising ceramic stain to be used in our ceramic industries. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17334 Bangladesh J. Sci. Ind. Res. 48(3), 213-216, 2013